Any effect of gymnastics training on upper-body and lower-body aerobic and power components in national and international male gymnasts? - Jemni, M.; Sands, W. A.; Friemel, F.; Stone, M. H.; Cooke, C. B. (The Journal of Strength and Conditioning Research, 2006)
Aerobic and anaerobic performance of the upper body (UB) and lower body (LB) were assessed by arm cranking and treadmill tests respectively in a comparison of national (N) and international (I) male gymnasts. Force velocity and Wingate tests were performed using cycle ergometers for both arms and legs. In spite of a significant difference in training volume (4-12 vs. 27-34 h/wk for N and I, respectively), there was no significant difference between N and I in aerobic and anaerobic performance. Upper body and LB maximal oxygen uptake (VO2max) values were 34.44 +/- 4.62 and 48.64 +/- 4.63 ml/kgmin vs. 33.39 +/- 4.77 and 49.49 +/- 5.47 ml/kgmin, respectively, for N and I. Both N and I had a high lactic threshold (LT), at 76 and 82% of VO2max, respectively. Values for UB and LB force velocity (9.75 +/- 1.12 and 15.07 +/- 4.25 vs. 10.63 +/- 0.95 and 15.87 +/- 1.25 Wkg) and Wingate power output (10.43 +/- 0.74 and 10.98 +/- 3.06 vs. 9.58 +/- 0.60 and 13.46 +/- 1.34 Wkg) were also consistent for N and I. These findings confirm the consistency of VO2max values presented for gymnasts in the last 4 decades, together with an increase in peak power values. Consistent values for aerobic and anaerobic performance suggest that the significant difference in training volume is related to other aspects of perfomance that distinguish N from I gymnasts. Modern gymnastics training at N and I levels is characterized by a focus on relative strength and peak power. In the present study, the high LT is a reflection of the importance of strength training, which is consistent with research for sports such as wrestling.